2017
DOI: 10.1039/c7ra10510j
|View full text |Cite
|
Sign up to set email alerts
|

The phase, morphology and surface characterization of Ti–Mo alloy films prepared by magnetron sputtering

Abstract: Magnetron sputtering is a physical vapor deposition process which allows the formation of metastable materials because of the particle bombardment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The Mo3d spectra of TMF MP and TMF EP ( Fig. 2 (j-k)) were fitted by components associated with metallic Mo (located at 227.0 eV-227.1 eV and at 229.8–230.4 eV) [ 38 , 54 ], MoO 2 (located at 228.6 eV-229.1 eV and at 231.5–232.3 eV) [ 38 , 55 ] and MoO 3 (located at 233.1 eV-234.1 eV and at 235.0–236.2 eV) [38] . The concentration of metallic Mo in TMF MP and TMF EP was 37.3 at.% and 33.5 at.%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Mo3d spectra of TMF MP and TMF EP ( Fig. 2 (j-k)) were fitted by components associated with metallic Mo (located at 227.0 eV-227.1 eV and at 229.8–230.4 eV) [ 38 , 54 ], MoO 2 (located at 228.6 eV-229.1 eV and at 231.5–232.3 eV) [ 38 , 55 ] and MoO 3 (located at 233.1 eV-234.1 eV and at 235.0–236.2 eV) [38] . The concentration of metallic Mo in TMF MP and TMF EP was 37.3 at.% and 33.5 at.%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is also consistent with the finding that the addition of alloying elements (e.g., Cr, Nb, Mo, etc.) promotes the stabilization of the β-phase in the Ti-based alloy films [26][27][28]. According to a previous study of Ti-Cr films, with the addition of ~10 at.…”
Section: Phase Analysis Of Ti-ni Filmsmentioning
confidence: 98%
“…Note that the increasing Cr content has little change in the modulus of Ti-Cr films, retaining the values at ~95 GPa. Liu et al [28] revealed the phase formation and morphology evolution of sputtered Ti-Mo films under different substrate temperatures. The Ti-15Mo film could retain the β phase at 50~100 °C, while the Ti-30Mo film could maintain the β phase at higher temperatures up to 300 °C.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of metastable metal alloys are known which can mainly be divided into groups such as supersaturated solid solutions, crystalline intermetallic compounds, quasicrystalline phases and metallic glasses. The main methods for the synthesis of metastable alloys are melt or solid quench (conventional casting, 1 rapid solidification, 2,3 laser pulse 4 ), condensation (vapor–gas, 5 sputtering, 6,7 electrodeposition, 8 chemical 9,10 ), irradiation (particle bombardment, 11,12 ion implantation, 13 ion beam mixing 14 ), mechanical cold working (ball milling, 15 cold rolling, 16 pressure 17 ) and solid-state reaction (multilayers, 18 single-source decomposition 19,20 ). Most of the works are devoted to the synthesis and study of metastable alloys in the form of thin films.…”
Section: Introductionmentioning
confidence: 99%